PlayMaker
PlayMaker® is a versatile new tool for teaching drills, tactics and plays in all sports at all levels. Exchangeable templates depict the field of play and the magnetic "ball" & "players" of two teams can be instantly organized and repositioned to illustrate the drill, tactic or play. Team lists, schedules, lines, times, statistics, etc. stay organized and handy. Designed by an active coach, PlayMaker® is the ideal combination of coach's clipboard, gameboard and file folder. It is indispensible for good organization and clear communication by coaches, teachers and parents before, during and after practices and games.